Pengawasan Syahbandar terhadap Pembuangan Limbah Kapal sebagai Upaya Pencegahan Pencemaran Laut: Studi Literatur - Nisa, Hanifah Aulia; Nazarwin, Nazarwin (Politeknik Pelayaran Sumatera Barat, 2025)
Marine pollution caused by ship waste discharge was one of the major environmental challenges in global maritime governance. The issue had significant ecological and socio-economic impacts, particularly in coastal regions. In Indonesia, the Harbormaster (Syahbandar) played a strategic role as the authority responsible for supervising ship operations, including waste management and discharge control. However, the effectiveness of Harbormaster supervision in preventing marine pollution had not been widely examined in academic research. This study aimed to systematically review and analyze the role and effectiveness of Harbormaster supervision in managing ship-generated waste as a preventive measure against marine pollution. The research applied a Systematic Literature Review (SLR) based on the PRISMA 2020 guidelines, combined with bibliometric analysis using VOSviewer software. A total of 25 scientific publications from 2018 to 2025 were selected using inclusion and exclusion criteria from databases such as Google Scholar, Scopus, and Web of Science. The analysis showed that the dominant research themes were related to MARPOL 73/78 implementation, Port Reception Facilities (PRFs), and port environmental supervision. The VOSviewer mapping revealed strong linkages among keywords such as MARPOL implementation, pollution prevention, port state control, and waste management, reflecting the growing importance of environmental governance in maritime operations. This study also highlighted the need for synergy between national regulations, institutional oversight, and digital monitoring technologies to ensure effective waste control at sea. The findings contributed conceptual and practical insights into how Harbormaster supervision could be optimized to strengthen maritime environmental governance. Enhancing the Harbormaster’s role was crucial not only for reducing ship-based pollution but also for supporting sustainable marine ecosystems and achieving UN Sustainable Development Goal (SDG) 14: Life Below Water.